Comparison of efficacy and safety of complementary and alternative therapies for essential hypertension with anxiety or depression disorder. - Xueyan Han; Xinxin Liu; Fengxing Zhong; Yiguo Wang; Qiming Zhang (PLoS ONE)
Background Essential hypertension (EH) with anxiety or depression belongs to the category of psycho-cardiology. Hypertension is closely related to anxiety and depression. The adverse reactions of Western medicine are apparent and the compliance is poor. Supplementary and replacement therapies have accumulated rich experience in clinical practices, which can reduce side effects and improve clinical efficacy. This study intends to use the Bayesian network meta-analysis (NMA) analysis method for the first time to gather randomized controlled trials (RCTs) related to complementary and alternative therapies in the treatment of hypertension with anxiety or depression disorder and rank efficacy and safety, to provide a reference basis for the treatment of hypertension with anxiety or depression disorder. Methods All randomized controlled trials (RCTs) and registered and ongoing trials of Chinese and English databases, related to supplementation and replacement therapies of EH with anxiety or depression disorder, published from initial state to February 2021, will be collected in the form of computer retrieval. Two researchers will independently screen the literature, extracting data, assessing bias risk and assessing heterogeneity. We will use software WinBUGS 1.4.3 and Stata 16.0 for pairwise meta-analysis and NMA to comprehensively evaluate various interventions. The quality of evidence will be evaluated through the Grading of Recommendations Assessment, Development and Evaluation (GRADE). Results This NMA will comprehensively compare and rank the efficacy and safety of a series of complementary and alternative therapies in treating EH with anxiety or depression disorder. Conclusion Supplementary and replacement therapies have accumulated rich experience of clinical practices in improving EH with anxiety or depression disorder. We expect that this NMA will guide practice and research by providing reliable evidence of evidence-based medicine for the treatment of EH with anxiety or depression disorder. Protocol registration number INPLASY202120068.